Discontinuation Rates of Tadalafil Alone and in Combination with a-Blockers in the Treatment of Male Lower Urinary Tract Symptoms with or without Coexisting Erectile Dysfunction: A Systematic Review and Meta-Analysis. (3rd November 2022) - Chen, Qiang; Mao, Yinjun; Zhou, Huiliang; Tang, Songxi
Abstract : Purpose . We examined the discontinuation rates of tadalafil alone and in combination with a-blockers (ABs) for the treatment of male lower urinary tract symptoms (LUTS), with or without erectile dysfunction (ED). Materials and Methods . We searched the EMBASE, PubMed, Web of Science, Scopus, Cochrane Library, and ClinicalTrials.gov databases for studies published until May 15, 2022. The discontinuation rates associated with LUTS medications were subsequently analyzed by meta-analysis. Results . Forty-four studies, including 1724 discontinued patients, were included. The combined discontinuation rate was 12.78% (95% confidence interval (CI) 9.89–15.98%), and the discontinuation rates because of adverse events and lack of efficacy were 4.56% (95% CI 3.39–5.90%) and 3.30% (95% CI 1.53–5.72%), respectively. Conclusions . The discontinuation rate of tadalafil alone or in combination with ABs for LUTS with or without ED was relatively low and varied according to the study type. Patients receiving monotherapy or combination therapy were similarly likely to abandon treatment. Treatment with a fixed-dose combination was associated with better persistence than with a free-dose combination. These data may help guide clinicians in selecting drug regimens when making decisions. Factors associated with treatment withdrawal need to be determined through high-quality clinical studies to reduce the drug discontinuation rate, which will ultimately reduce healthcare costs and improve patient outcomes.